Enabling environment for waste and wastewater recycling and reuse options in South Asia: The case of Sri Lanka - Maksud Bekchanov (University of Bonn, Center for Development Research (ZEF), 2017)
Mismanagement of waste and wastewater is a key reason behind the continuing environmental pollution and degrading livelihoods across the developing countries of South Asia such as Sri Lanka. Recovering nutrients and energy from waste and wastewater streams can not only address the challenging waste and wastewater management problems but also considerably substitute the imports of chemical fertilizers and fossil fuels. Considering these environmental and economic benefits of waste and wastewater recycling, this study aims at assessing investment climate for a broader implementation of recycling technologies such as composting, biogas generation, and electricity production through incineration process. For this purpose, a wide range of methods were implemented including a detailed review of scientific literature, laws and reports by governmental agencies, as well as key informant interviews and focus group discussions. For assessing technical potential of recovering nutrients from waste streams a simulation model was applied. As results indicated, since waste generation and thus potential for nutrient recovery is high in urban areas, while demand for recovered nutrients is much higher in rural areas, interregional trade of the recovered nutrients would considerably contribute to reducing the shortage of fertilizers, improving food security, and increasing export incomes in Sri Lanka. Recovering nutrients from recycling only half of total organic waste and wastewater may allow for meeting agricultural demands for phosphorus and potassium, and supply 75% of nitrogen requirements at the national level. The government would need to be the main facilitator of the change through improving the accounting and planning in the system, establishing effective institutional and regulatory frameworks, providing financial incentives for the implementation of the recycling technologies, and supporting educational programs for raising the environmental consciousness.
Keywords: Q42; Q53; Q55; 330; Resources recovery and reuse (RRR); composting; biogas generation; incineration; fertilizer demand